Grip strength in young tennis players: Normative values and predictors of performance - Novak, D.; Viboh, V.; Barbaros, P.; Bilic, Z.; Markovic, G. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The objectives were to (a) establish normative grip strength values in young tennis players; (b) examine developmental changes across 4 adolescent age groups and sexes, controlling for maturity and body size; (c) assess the association between body size and grip strength independent of age and maturity; (d) evaluate grip strength`s ability to distinguish successful from less-successful players, independent of age, maturity, and body size; and (e) compare dominant and nondominant hands to identify tennis-related lateral differences.